Implementation of Green Politics Theory in Green Sister City Cooperation - Damayanti, Rizka Dwi; Sagena, Uni W. (LifeSciFi, 2025)
The Sister City partnership between Surabaya and Kitakyushu, established in 1997, has become a vital driver of sustainable development with a strong emphasis on environmental conservation and economic inclusivity. Grounded in Green Political Theory, this collaboration translates sustainability principles into actionable initiatives addressing pressing environmental issues while fostering socio-economic growth. This qualitative study explores the impacts and outcomes of the Surabaya-Kitakyushu partnership through methods such as document analysis and stakeholder interviews. It evaluates strategies, initiatives, and partnerships developed under the Sister City framework, highlighting their effectiveness and challenges. Central to this collaboration are commitments to ecological responsibility, social equity, and inclusive economic development. Notable initiatives include the Takakura composting method and the